Mechanical and thermal properties of hybrid nanocomposites prepared by in situ polymerization - Paszkiewicz, S.; Pawelec, I.; Szymczyk, A.; Rosłaniec, Z. (Polimery, 2021)
Poly(trimethylene terephthalate) (PTT) nanocomposites containing carbon nanoadditives which differ in shape (1D, 2D) and particle size were synthesized by in situ polymerization method. SEM and TEM images showed that expanded graphite (EG) and single-walled carbon nanotubes (SWCNTs) were well dispersed in PTT, suggesting that in situ polymerization is a highly efficient method for preparing nanocomposites. Synergistic effect between single-walled carbon nanotubes and expanded graphite on improving mechanical and thermal properties of the prepared nanocomposites has been observed.